Disability gap in access to education for children and adolescents in Argentina (Desarrollo Económico. Revista de Ciencias Sociales, 2024)
One in ten children and adolescents worldwide live with disabilities and they represent one of the highest percentages of the out-of-school population. This article estimates the disability gap in access to education for children and adolescents in Argentina based on the UNICEF’s Multiple Indicator Cluster Survey (MICS) carried out in the country in 2019-20. The results indicate that children and adolescents with disabilities are nearly 2 percentage points less likely to attend school than their peers without disabilities. The estimated disability gaps were larger for children and adolescents of lower secondary school age (12-14 years old), and for those with mobility, visual and intellectual impairments. Results also show a gap in the probability of enrollment using an alternative definition of disability, based on disability certificate.
Keywords: Disabilities, Educational Attendance, Child and Adolescence, Argentina